Organology of Gong Gumbeng Instrument in Wiringanom Village Sambit Ponorogo - Sari, Monika Dewi Indah; Nur Salim, Muhammad (Universitas Negeri Semarang, 2025)
This research aims to determine the organology of making Gong Gumbeng from the beginning until it can be used. The problem focuses on (1) the process/stages for selecting the materials and tools. (2) Second, what is the process of making Gong Gumbeng (3) Third, what is the process of aligning the Gong Gumbeng (4) Fourth, what is the function of the Gong Gumbeng in the Wringinanom community. To approach this problem, a theoretical reference from Sri Hendarto entitled Organology and Acoustics I&II is used, which in the book reveals the materials and tools used in making a musical instrument, the process of making a musical instrument, tuning musical instruments, and the function and role of musical instruments. The method used in this research is qualitative research with descriptive analysis. Data was collected through observation, interviews, and literature study. This study concludes that the Gong Gumbeng is an important musical instrument for the Wringinanom people. This research also reveals the process of making the Gong Gumbeng musical instrument, the tools and materials used, the tuning process, and the role and function of the Gong Gumbeng musical instrument for the Wringinanom community.